SUMO ligase PIAS1 functions as a target gene selective androgen receptor coregulator on prostate cancer cell chromatin - Toropainen, Sari (Nucleic Acids Res, 2015)
Androgen receptor (AR) is a ligand-activated transcription factor that plays a central role in the development and growth of prostate carcinoma. PIAS1 is an AR- and SUMO-interacting protein and a putative transcriptional coregulator overexpressed in prostate cancer. To study the importance of PIAS1 for the androgen-regulated transcriptome of VCaP prostate cancer cells, we silenced its expression by RNAi. Transcriptome analyses revealed that a subset of the AR-regulated genes is significantly influenced, either activated or repressed, by PIAS1 depletion. Interestingly, PIAS1 depletion also exposed a new set of genes to androgen regulation, suggesting that PIAS1 can mask distinct genomic loci from AR access. In keeping with gene expression data, silencing of PIAS1 attenuated VCaP cell proliferation. ChIP-seq analyses showed that PIAS1 interacts with AR at chromatin sites harboring also SUMO2/3 and surrounded by H3K4me2; androgen exposure increased the number of PIAS1-occupying sites, resulting in nearly complete overlap with AR chromatin binding events. PIAS1 interacted also with the pioneer factor FOXA1. Of note, PIAS1 depletion affected AR chromatin occupancy at binding sites enriched for HOXD13 and GATA motifs. Taken together, PIAS1 is a genuine chromatin-bound AR coregulator that functions in a target gene selective fashion to regulate prostate cancer cell growth.